Big data – BigData 2018 : 7th International Congress, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings /: 7th International Congress, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings. (2018) - Unknown
No abstract available